2021
DOI: 10.3389/fimmu.2021.626884
|View full text |Cite
|
Sign up to set email alerts
|

Role of Primary Afferents in Arthritis Induced Spinal Microglial Reactivity

Abstract: Increased afferent input resulting from painful injury augments the activity of central nociceptive circuits via both neuron-neuron and neuron-glia interactions. Microglia, resident immune cells of the central nervous system (CNS), play a crucial role in the pathogenesis of chronic pain. This study provides a framework for understanding how peripheral joint injury signals the CNS to engage spinal microglial responses. During the first week of monosodium iodoacetate (MIA)-induced knee joint injury in male rats,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…DRG (and spinal cord) changes have been recently recognized to be associated with pain chronicity in OA, especially at the advanced stage of disease [ 49 ]. More recent literature has documented profound molecular and cellular changes in the DRG of various OA models, including changes in neuronal excitability [ 50 ], intense proliferation and activation of microglia that mediate neuroinflammation, and neuronal damage [ 15 , 51 53 ], transcriptomic upregulation of the genes for neuroimmune interactions [ 54 ], sensitized PSN nociceptive voltage-gated ion channels [ 16 , 55 ] and mechanosensitive ion channels [ 42 ], and upregulated chemokine and cytokine production [ 56 ], all contributing interrelatedly in driving continuous neural sensitization after cessation of joint inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…DRG (and spinal cord) changes have been recently recognized to be associated with pain chronicity in OA, especially at the advanced stage of disease [ 49 ]. More recent literature has documented profound molecular and cellular changes in the DRG of various OA models, including changes in neuronal excitability [ 50 ], intense proliferation and activation of microglia that mediate neuroinflammation, and neuronal damage [ 15 , 51 53 ], transcriptomic upregulation of the genes for neuroimmune interactions [ 54 ], sensitized PSN nociceptive voltage-gated ion channels [ 16 , 55 ] and mechanosensitive ion channels [ 42 ], and upregulated chemokine and cytokine production [ 56 ], all contributing interrelatedly in driving continuous neural sensitization after cessation of joint inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, glial cells are robustly activated in injured or diseased states and are involved in a variety of neuropathological changes, including chronic pain [44]. It was reported that early activation of joint nociceptors after injury triggers spinal microglial activation [45]. Microglia release cytokines (such as TNF-α and IL-18), growth factors (such as BDNF), and ATP, which in turn stimulates astrocytes and neurons to induce central sensitization [46].…”
Section: Discussionmentioning
confidence: 99%
“…No animals exceeded these limits. The MIA dose was based on previous studies 25 , 40 and on a pilot study (Figure S1, http://links.lww.com/PR9/A224 ). Intra-articular injection of 2 mg/50 µL of MIA produced robust pain behavior and OA-like knee pathology in young adult female Sprague-Dawley rats, while a 1 mg dose produced variable joint pathology without significant pain behavior.…”
Section: Methodsmentioning
confidence: 99%
“…No animals exceeded these limits. The MIA dose was based on previous studies 25,40 and on a pilot study (Figure S1, http://links. lww.com/PR9/A224).…”
Section: Induction Of the Monosodium Iodoacetate Model Of Osteoarthri...mentioning
confidence: 99%